Strategy of Innovation for the Productive Linkage - Solana-Garzón, José Manuel; Herrera-Capdevilla, Pablo (EFIM Ediciones, 2020)
Currently, phenomena such as globalization and the economic interdependence of countries have made the requirements in goods and services in optimal conditions to meet world demand. These requirements have made the economy to be oriented towards the commodities that set the world standard, as is the case of oil and its derivatives. Thus, many companies linked to this sector require a sectorial strategy of innovation in accordance with current needs. One of these strategies is related to maintenance as a fundamental axis to guarantee the operation, that is why fundamental needs arise in the organizations that carry out petrochemical processes, to have suppliers that can satisfy those needs. That is why we propose the design of a sectorial strategy in innovation in the competitive maintenance cluster in order to strengthen the productivity and competitiveness of the organizations and actors that are part of it. The most relevant fndings are linked to gap analysis, evaluation of technological trends and a defnition of a technology management plan and cluster development. This proposal is based on the models of productive chaining and is based on the theories of research and innovation strategies for intelligent specialization RIS3, business innovation capabilities, business strategy.